Past antihypertensive drugs, obesity, daily light working load and risk of hypertension: An Indonesian 2001 rural study (Medical Journal of Indonesia, 2001)
This study aims to identify some risk factors related to hypeertension in rural areas. The data for this study is a part af the result of the field study done by the second year medical students of the Faculty of Medicine, University of Indonesia, Jakarta, on June 27h , 2001, at Cijeruk subdistrict in Bogor regency. The subjects were seleccted randomly using neighborhood cluster which was diffirent from the previous study in 2000. Interviews and blood pressure were taken at the houses of the subjects from 1:00 PM to 4:00 PM. The results of this study showed that people aged 40 years or over had an increase risk to suffer hypertension compared to the 18-39 year old group, and the risk was most prominent among the 55-59 year group [adjusted odds ratio (OR)= 17.7; 95% confidence intervals (CI)=6.26-59.2). Compared to the subjects with normal body posture,those who were obese had more than two-fold increase in the risk to be hypertensive (adjusted OR= 0.87; 95% CI= 0.87-4.17; P= 0.109). In addition, those who discontinued antihypertensive drugs had almost 14-fold increase in the risk to be hypertensive relative to subjects who never take antihypertensive drugs (adjusted OR= 14.16; 95% CI= 7.14- 28.05). In general, the results of this study is similar with our last year study which used different subjects. This study concluded that special attention should be taken to the elderly aged 40 years and over, to some one who discontinued antihypertensive drugs; andwhom had light daily working load to prevent hypertension. (Med J Indones 2001; 10: 224-9)